Environmental ethics in Islam : protection and sustainability of the ecosystem - Fatimah Nazifah binti Kamarudin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The alarming issues of environmental crisis in modern days have resulted in great interest with the discussions and studies of ethics towards the environment. As a consequence, we are witnessing the growth of the Environmental Ethics discipline. Religious teachings are utilised as a significant reference of knowledge in the development of this discipline. This research studies the Environmental Ethics in Islam with a special focus on the protection and sustainability of the ecosystem. It attempts to analyse the concept of environment and ecosystem as well as the relationship between human beings and nature in Islam. This study also discusses the Islamic concept of virtues and vices as the basic principles for Islamic environmental ethics and how these concepts play a major role in shaping human behaviours towards the environment. The thesis, which is based on library research, is divided into six chapters. They propose practical measures for the environmental protection and sustainability as well as highlight the Islamic views on the environment. The study arrives at the conclusion that Islamic teachings can contribute significantly towards the overall environmental awareness and the protection of the ecosystem.